PERANAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU DI MADIN SAHLAH PARE KEDIRI - Puji Rahayu (UII Darullughah Waddawah Pasuruan, 2023)
This study aims to: analyze the role of the madrasa head in improving the quality of madrasas at the sahlah pare madrasah This study uses a qualitative approach method. The research subjects were madrasa heads and teachers. Methods of data collection using interviews, observation, and documentationData analysis techniques using qualitative data analysis. The results of this study explain that the madrasah head as a manager has the role of creating an organizational structure and inviting parents of students to the madrasah committee program and completing the required supras; designing programs by outlining the needs of educators and educators who carry out their duties, designing the implemented curriculum; supervising output, teaching and learning process, and students from admission to completion; lifelong education As for the obstacles faced are the lack of teaching and learning facilities and infrastructure, there are still undisciplined educators and teaching staff, and the lack of communication between the head of the madrasa and several educators and teaching staff. Good madrasah managerial management will produce good quality education which will certainly affect learning outcomes and school achievement. The results of this study show that a program is still needed to improve the quality of education, both related to learning and not.